SECURIZAREA FRONTIERELOR REPUBLICII MOLDOVA: REALITĂŢI ŞI PERSPECTIVE - Cernov, Alexei (CEP USM, 2013)
The article analyzes an important issue for the Republic of Moldova: security of borders, that has a huge impact in geopolitical and geostrategical area. This issue affects national interests and external policy of republic. The autor analyzes some aspects of the transnistrian conflict and the ways to solve it.
Keywords: securizarea frontierelor